Training and Coaching Model Design as A Solutions for Women’s Microentrepreneurs Community (KOTA PELANGI) Problems - Nurul Asiah; Wahyudi David; Tuti Widiastuti (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2021)
Microentrepreneurs activities contribute to economic growth and social empowerment. KOTA PELANGI is one of women’s microentrepreneurs community that actively works to empower women in South Jakarta. Nevertheless, this community faces problems and limitations. The objective of this study is to design proper training and coaching as a solutions of those problems. The activities were conducted by data and information collections, field survey, observation, exploration, and design of the program. Results showed that more than 50% of community members work in the food business area. There are five priority problems faced by this community: marketing strategy, product quality and innovation, capital, equipment and facilities, employee and business management, business certification, and packaging. The model designed to solve each problem by training, coaching, and monitoring which is supported by various programs. The programs designed to solve the problems and increase the knowledge of community members, so they can manage their business better.